Empreendimentos hidrelétricos e transformações socioespaciais : a construção dos AHE Corumbá III e IV e os efeitos sobre o produtor rural diretamente atingido do município de Luziânia-GO - Oliveira, Luiz Fernando da Silva (2016)
This research reflects a study of grand hydropower plants in the county of Luziania, Goias state, where are found two of them in Corumba river: the stations III e IV. The research aims discuss the cause effects from these infrastructures on the territory, and seek to comprehend the social spatial changing occurred by those ones. Through the large range effects caused by these hydropower plants, we decided focus on the rural producer changing directly affected, which means, those who had their properties affected partially or totally by the dam. Therefore, it was approached three geographical concepts about one of the most Territory theory discussed in Brazil: territorialização, desterritorialização e reterritorialização. They conceive different perspectives about how the rural producers overlapped, moved out and (re)overlapped the affected lands, respectively, making possible the comprehension of the physical space and social organization changed by the effects. As a methodological procedure, initially were raised data s and discussed a relevant literature review for the research, beyond the historic process evolution about the hydroelectric sector in the country. Afterwards, were described with emphasis in the changing caused by the stations in the county of Luziânia, which supported the grand plants discourse concepts in Brazil, valid to other researches and projects as well. The effects caused to the rural producers are, mostly, results that run beyond the population interests. Therefore, in name of the improvement and economic development of the country, these populations have suffered several negative aspects, that appear on their territory and everyday life.